Current status of PTSD treatment and exploration of painting therapy - Li, Lu; Ibrahim, Rahinah; Azmi, Athira; Abdul Shukor, Shureen Faris (Academia Industry Networks, 2022)
The objective of this paper is to study the corresponding painting treatment methods based on the application of painting therapy in PTSD, aiming to promote the application of painting therapy for PTSD and improve the cure rate of PTSD patients on the premise of meeting the needs of patients. Methods The concept of PTSD was analyzed through a literature review, and then the clinical symptoms of PTSD were summarized. Compared with traditional methods of treating PTSD, the advantages of painting for PTSD were found, and the possibility and development direction of painting for PTSD were explored. Conclusions By studying the painting treatment method of PTSD, the treatment experience of patients can be improved. Compared with the traditional treatment method of PTSD, effective painting treatment application and PTSD treatment can supplement the treatment method and improve the treatment effect, which has certain reference value for the research and treatment of PTSD.